Key Lessons from the PilotProgram for Climate Resilience : A Practical Resource for All Involved with Strategic Planning Processes and Mainstreaming of Climate Resilience - Rigaud, Kanta Kumari; Hoffer, Ronald; Ahmed, Kazi Fateha; Chaturvedi, Akshat; Gaensly, Laura; Kapila, Shaanti; Shrestha, Junu (World Bank, Washington, DC, 2020)
The top 10 Key Lessons from the PPCR highlight critical and strategic aspects that need to be considered in resilience planning and implementation. These lessons underscore the importance of institutional arrangements; information on climate vulnerabilities; leveraging finance; transforming at scale; engaging stakeholders; dedicated learning fora; engaging private sector; core indicators and monitoring; responsiveness to country context; and where relevant regional programming. These findings and observations are not theoretical but based on real experiences of country counterparts and multi-lateral development bank (MDB) teams over the planning and early implementation phase of the PPCR. The Knowledge Product (KP) also provides links to detailed supporting materials for optimal use of the information in your work.